Ten-year trajectories of ultra-processed food intake and prospective associations with cardiovascular diseases and all-cause mortality: findings from the Whitehall II cohort study - Mengmei E. Wang; Clare H. LIewellyn; Michail Katsoulis; Tasnime N. Akbaraly; Samuel J. Dicken; Jiahao Liu; Adrian Brown; Annie Britton (Nutrition Journal)
Abstract Background Ultra-processed food (UPF) intake has been associated with adverse health outcomes; however, research on UPF intake and cardiovascular disease (CVD) prognosis has largely neglected its longitudinal pattern over time. This study investigated trajectories of UPF intake over a decade and their prospective associations with the risk of fatal and non-fatal CVD, as well as all-cause mortality, using data spanning from 16 to 19 years. Methods This study utilized data from the British Whitehall II cohort study, including 7,138 participants (68.3% male; median baseline age 60.4 years), all free of CVD at baseline. Dietary intake was assessed using a validated 127-item food frequency questionnaire at three time points: phase 3 (1991–1994), phase 5 (1997–1999), and phase 7 (2002–2004). UPF intake was estimated using the Nova classification, and group-based trajectory modelling identified different longitudinal consumption patterns. Phase 7 (2002–2004) was the baseline for subsequent monitoring of cardiovascular events and mortality outcomes until 2019/2021. Multivariate Cox proportional hazards models were used to estimate the hazard ratios (HRs) and 95% confidence intervals (CIs), adjusting for socio-demographics, lifestyle, diet quality, energy intake, and clinical factors. Results Three distinct UPF trajectory groups were identified: high (26.2% of participants), moderate (52.9%) and low UPF intake (20.9%). All groups showed a slight increase in UPF intake over time. Over the median follow-up of 16 years for incident cases and 19 years for mortality, we observed 1,128 incident CVD events, 859 CHD cases and 1,314 deaths. The highest vs. lowest UPF intake group had a 23% higher risk of CVD (HR 1.23, 95% CI 1.01 to 1.40), and a 32% higher risk of CHD (HR 1.32, 95% CI 1.06 to 1.65). No significant associations were observed between UPF trajectory groups and CVD mortality, CHD mortality, or all-cause mortality. Conclusions Sustained high UPF intake over 10 years was associated with increased risks of non-fatal CVD and CHD but not with CVD-specific, CHD-specific, or all-cause mortality. These findings suggest that sustained high intake of UPF may be a modifiable risk factor for preventing non-fatal cardiovascular risks.